A 3D Peridynamic Model to Simulate Indirect Tensile Failure in Marble - Wenwu Tan; Keping Zhou; Shitong Zhou; Weicheng Ren (Geofluids)
Driven by the commitment of achieving peak carbon dioxide emissions before 2030 and carbon neutrality before 2060, China is promoting the optimization of its energy and industry structures. In the electricity supply industry, a large number of different types of sophisticated large and giant hydropower stations are planned or being constructed in western China. In future decades, hydropower may take the dominant position in China’s electricity supply. Rock fracturing behavior plays a vital role in geotechnical hazard prevention and geotechnical engineering design. With the construction of hydropower stations, rock mechanics investigation will be of great concern. This study presents a hybrid model that coupled the finite element method and peridynamic theory to simulate the indirect tensile strength of marble. Sensitivity analyses of the loading rate, mesh size, and fracture energy release rate are performed. The numerical results indicate that both the loading rate and mesh size significantly affect the numerical representation of rock properties. After the calibration of the fracture energy release rate, Brazilian tensile strength modeling is successfully conducted, and the numerical results are consistent with the experimental results.